Socioeconomic Adversity and Women’s Sleep: Stress and Chaos as Mediators - El-Sheikh, Mona (Behav Sleep Med, 2014)
We examined income-to-needs ratio, perceived economic well-being, and education and their relations with European and African American women’s sleep (n = 219). Sleep was examined through actigraphy and self-reports. Income-to-needs ratio was related to sleep minutes. Perceived economic well-being and education were associated with subjective sleep problems. Perceived stress mediated relations between both income-to-needs ratio and economic well-being and subjective sleep problems. Chaos emerged as a mediator linking income-to-needs ratio and subjective sleep problems. African American women had fewer sleep minutes and lower sleep efficiency than European Americans, and more robust relations between economic well-being and stress was observed for European Americans. Findings highlight the importance of economic adversity for women’s sleep and explicate some pathways of risk.